PERANAN GURU AGAMA KATOLIK DALAM MENINGKATKAN MUTU DAN PENGHAYATAN IMAN SISWA SEKOLAH MENENGAH TINGKAT ATAS KOTA MADIUN MELALUI PENGAJARAN AGAMA KATOLIK - Klementino Datus; Ola Rongan Wilhemus (Lembaga Penelitian STKIP Widya Yuwana, 2019)
Catholic religious teachers are the teachers for Catholic students at the senior or high school. The teachers are called to perform the duties as Catholic religiousteachers. Aside of teaching Catholicism, Catholic religious teachers are carried out their duties as the builder of the faith of senior high school student school.The formulation of this research problem are: who is the Catholic religious teacher, what is the duty and responsibility of the Catholic religious teacher, who arethe high school students, what is the teaching of Catholic religion, how is the impact of Catholic teaching on the development of religious knowledge and faith of Catholichigh school students. While the purposes of this study are to describe who is a Catholic religious teacher, to describe the duties and responsibilities of Catholic religious teachers, to describe who are the high school students, to analyze the content of Catholic teaching, and to identify the impact of Catholic teaching on the development of knowledge and understanding of the faith Senior High School students. The results of the study showed that 3 (60%) of the respondents perceived Catholic religious teachers as teachers who were trusted to teach the students about who is Jesus Christ, God, and Church. Then 5 (100%) of respondents believe that the duty and responsibility of Catholic religious teachers is to teach the Catholic faith, to strengthen the catholic moral values of the students and to teach the students to believe the teachings of Jesus Christ. Then 2 (40%) respondents said that students of Senior High School were students who start to be critical and mature, 4 (80%) respondents believed that the teaching of Catholic religion done by a Catholic religious teacher was aimed to transfer the knowledge related to Catholic religion to the students in order to reinforce their faith.